P5-S4.05 The use of financial compensation as an incentive for infectious syphilis case finding among vulnerable populations in Edmonton, Canada. (10th July 2011) - Gratrix, J; Fan, S; Anderson, B; Conroy, P; Hewitt, S; Parnell, T; Jaipual, J; Parker, P; Singh, A E; Talbot, J
Abstract : Background: Edmonton, Canada has been experiencing a rise in infectious syphilis cases since 2003, attributed to individuals engaging in transactional sex and substance use. As well, Aboriginal people had disproportionately higher rates of the infection. The results of a case study of primary syphilis cases were shared with community organisations serving vulnerable populations to ascertain their suggestions on strategies to increase testing for syphilis among this population. Agencies suggested that compensating clients for syphilis screening at a community organisation would increase testing rates. We sought to determine if more cases among the target population were diagnosed through outreach testing that provided financial compensation than by routine screening methods by other healthcare professionals. Methods: A data extract containing demographics, ethnicity, and risk behaviours for infectious syphilis cases in Edmonton between April 2007 and November 2008 was obtained from the provincial STI database. An additional database, which held demographic and risk group information on participants in the project, was also analysed. Client demographics and risk behaviours were compared using χ 2 or Fisher's exact test for categorical variables and Mann–Whitney for continuous variables. Results: A total of 931 testing visits were completed with 877 individuals. Three-quarters of individuals reported a history of substance use (77.1%; n=676) with more than one-quarter of individuals involved in transactional sex, either as a sex worker (n=204) or contact with a sex worker (n=110). Over half of the individuals (51.3%; n=450) were Aboriginal. Ten newly diagnosed infectious syphilis cases were found. The proportion of cases detected among female sex workers was 2.9% (6 cases out of 209 testing visits) and was 2.0% (2 cases out of 98 testing visits) among male sexual contacts of sex workers. Female cases were more likely to be a sex worker when tested through outreach (75%) than by routine testing sites (23.5%, p=0.006) see Abstract P5-S4.05 table 1 . Conclusions: By offering testing at community agencies with financial compensation to individuals, a higher rate of cases were found among sex workers than through routine testing methods. By treating cases among individuals linked to high transmission activity, we aim to reduce the transmission of infectious syphilis.